2016
DOI: 10.1177/0193945916654666
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Psychological Health

Abstract: This study tested the mediating role of primary (e.g., threat and challenge perceptions) and secondary (e.g., coping potential and control perception) cognitive appraisal in the relationship between occupational stress and psychological health. This mediation was tested using a cross-sectional study based on self-reported measures. The total sample consisted of 2,302 nurses, 1,895 females (82.3%) and 407 males (17.7%), who completed an evaluation protocol with measures of occupational stress, cognitive apprais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Prior research found that perceived severity of COVID-19, as a negative appraisal of the event, was associated with more undesirable emotional and behavioral outcomes [ 1 ]. This result is also consistent with the findings that negative evaluation of an event, such as high levels of perceived severity, is associated with negative mental health outcomes when individuals encounter a novice virus [ 5 , 7 , 24 ]. Deepening our understanding of this association, the current study sought to examine self-control as a candidate to moderate the link between perceived severity and mental health problems among the Chinese public.…”
Section: Discussionsupporting
confidence: 90%
“…Prior research found that perceived severity of COVID-19, as a negative appraisal of the event, was associated with more undesirable emotional and behavioral outcomes [ 1 ]. This result is also consistent with the findings that negative evaluation of an event, such as high levels of perceived severity, is associated with negative mental health outcomes when individuals encounter a novice virus [ 5 , 7 , 24 ]. Deepening our understanding of this association, the current study sought to examine self-control as a candidate to moderate the link between perceived severity and mental health problems among the Chinese public.…”
Section: Discussionsupporting
confidence: 90%
“…As expressed in Hypothesis H4, the mediation might be partial, which can be expected from prior research, where direct effects between stressors and health-related outcomes were still confirmed when analyses were adjusted for stressor appraisal (Gomes et al 2016;Webster et al 2011), leading to the conclusion that working conditions can also be harmful for health regardless of their subjective evaluation. Therefore, a direct path between the exposure to work demands and the outcome variables is included in the conceptual model ( Fig.…”
Section: H4mentioning
confidence: 60%
“…Oliver and Brough (2002) revealed that perceived controllability were predictive of individuals' well-being. In another research, Gomes, Faria, and Lopes (2016) found that perceptions of threat, control, and challenge of stressful encounters were significantly related to mental health problems. Besides, cognitive appraisal has also been applied to the study of the public's emotion and behaviour during the outbreak of emergent public health concerns.…”
Section: Cognitive Appraisal and Emotion And Behaviourmentioning
confidence: 96%